On the impact of inequality on investment and occupational choice under imperfect capital markets - Yu, Zhongjian (2012)
Direct finance such as stock and bond markets has provided an alternative source of funds for a large number of firms, which depends heavily on bank loans for credit previously. Bank loans are more expensive indeed than direct finance so that only those borrowers cannot access to capital markets turn to it. Such co-existence of alternative sources of finance has supplied prevalent issues for researches. The thesis focuses on investment choice and the selection of occupation with finance restriction under co-existence of finance sources. We also investigate the impact of inequality in imperfect markets.